The Effectiveness of Online Learning With E-Learning Madrasah at MA Muhammadiyah Nangahure - Taufik, Rahman (EDUCTUM: Journal Research, 2022)
This study aims to determine the effectiveness of online learning using Madrasahi E-Learning Media MA Muhammadiyah Nangahure. This research method uses qualiative research by explaining the data obtained from the results of the effectiveness of online learning using madrasa e-learning. Data collection techniques using interviews obtained directly from informants (primary sources). The sampling technique is carried out by the random sampling method where each informant from the population has the same opportunity to choose a sample. The results showed that learning using madrasa e-learning is quite effective to implement. Although there are still obstacles encountered when learning using madrasa e-learning such as network constraints or locations that are not reached by networks, but all parties try their best to work on so that the obstacles can be overcome.